Dzieci z rodzin zastępczych w szkole. Raport o współpracy rodziców zastępczych z personelem szkoły - Katarzyna Ćwirynkało; Urszula Bartnikowska (Problemy Wczesnej Edukacji)
Children and youth from foster families more often – in comparison to general population – have disabilities, emotional and behavioural disorders (Minnisi in. 2006). Also, in their history of life they often experienced abuse and/or neglect, which may influence their later achievements (Kolankiewicz 2009; Bartnikowska, Ćwirynkało 2016). Foster parents often deal with challenges connected to raising their children. The paper is a research report in which the authors investigate the perceptions of foster parents concerning their cooperation with teachers and school personnel. In order to achieve this aim an interpretivist paradigm and phenomenographic method (Paulston 1993) was applied. Three focus group interviews were conducted with 21 foster parents of children and youth at school age. A qualitative analysis (Charmaz 2009) resulted in the identification of two thematic areas of parents’ perceptions of: (1) division of responsibility (perception of the role of a foster parent and school personnel in the process of their children’s education), (2) positive and negative aspects of foster parents’ experiences in the cooperation with school (personal and organizational level). Based on the results, recommendations on how to improve the cooperation between school and foster parents are proposed.